Вера, Надежда, Любовь...: женские портреты : [25 знаменитых женщин последних двух столетий] / Ю. Безелянский - Безелянский Юрий Николаевич (Радуга, 1998)
Экземпляры: аб. (2000) / Инвентарный номер: 42420 / Цена: / Сис.шифр: 63.3(2)5 / Авт.знак: Б 39 / ГРНТИ: 03.23 / ББК: 63.3(2)5-297